NEW TECHNOLOGIES OF PRODUCTION OF CAST GRIT OF IRON-CARBON ALLOYS - D. A. Volkov; A. P. Melnikov; P. S. Gurchenko; A. D. Volkov (Литьë и металлургия)
New technologies of production of cast grit of iron-carbon alloys are given